Digital Banking, Fintech Payment, and Fintech Lending Influence the Financial Performance of Conventional Banking - Kirowati, Dewi; Anggraeny, Shinta Noor; Lakew, Tayech (Accounting Study Programme Faculty of Economics and Business Universitas Negeri Surabaya, 2025)
Background Problems: The rapid growth of financial technology (fintech) has transformed the operational landscape of conventional banking, reshaping how financial services are delivered and managed. Introduction/Main Objectives: This paper examines the relationship between digital banking, fintech payment, fintech lending, and the financial performance of conventional banks in Indonesia. Methods: Secondary data for the 2018–2022 period were collected from the Financial Services Authority (OJK), Bank Indonesia, and the Indonesia Stock Exchange (IDX) for this study, the study employs multiple regression analysis to evaluate how digital transformation affects profitability, efficiency, and competitiveness in the traditional banking sector. Results: The findings reveal that digital banking and fintech payment have a significant positive impact on bank performance, indicating that technology adoption enhances operational effectiveness and revenue diversification. Conversely, fintech lending exhibits a moderating influence by expanding credit accessibility while intensifying competition in loan markets. Conclusion: Overall, the results highlight that strategic bank–fintech collaboration and proactive digital adaptation are essential to achieving sustainable growth and maintaining competitive advantage in the era of financial digitalization.